The synaptic vesicle cycle: a molecular overview - Arisi, Gabriel M. Arisi M.; Neder, Luciano; Moreira, Jorge E. (Medicina (Ribeirao Preto), 2001)
The present review approaches a specific point in the synapse, probably the main one: the molecular interactions between the synaptic vesicle proteins and the presynaptic membrane proteins. A very precise language is talked between the vesicular and presynaptic membranes that allow the neurotransmitter release to the synaptic cleft. In recent years, the synaptic vesicle has been molecularly dissected, and it is probably the cell organelle with the most complete structural and kinetical description of its protein components. The discovery of families of homologue proteins in all eucariotic cells such as Rabs and SNAREs (SNAP receptors), demonstrated that the synaptic vesicle cycle depends on a refined interaction between a specific and universally distributed system of proteins that regulates the vesicle motion and fusion. The kinesin family is in charge of the mechanics for the anterograde transport of the raw material from the neuronal soma along microtubules in the axonal cytoskeleton. Sorting and flux control of the synaptic vesicle structural precursors is done by the Rab family of small GTPases. SNARE proteins make the fusion of the vesicles with the presynaptic terminal. Synaptotagmin regulates the formation of the SNARE complex in a calcium dependent mode. Although many of these proteins and their functions are well known, there is a large segment of knowledge on structure and interactions yet to be known.